How to make money marketing your Android apps : understanding Google's open sales model - Hughes, Jeffrey (FTPress, 2011)
A complete plan for selling your Android apps -- including little-known techniques based on Google's unique "open selling model". Unlike Apple, Google allows developers to market their Apps from any site, including your own, not just Android Market. Google's open sales model, while still maturing, can provide advantages over Apple's closed model -- if you take advantage of the options Google gives you. This paper identifies key marketing activities that can help you succeed.